Peningkatan Hasil Belajar Gerak Dasar Lari Melalui Permainan Hijau Hitam (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
This study aims to improve the learning achievement of the basic running problem in this study is "Are black green game in Class 3 of SD Negeri 01 Sirangkang Petarukan Pemalang academic year 2013/2014. Type ofresearch is Classroom Action Research that consists of 2 cycles, each cycle consisting of planning, action,observation, and reflection. The study was conducted in SD Negeri 01 Sirangkang Petarukan Pemalang,research subjects from grade 3 by 27 students consisting of 10 boys 17 student girl. The results showed thatstudent achievement is not yet complete on prasiklus there are 12 students or 44.44%, on cycle 1 has decreased29.63% and a decrease in cycle 2 to 3 students or 11.11%. Student achievement that has been completed onprasiklus there are 15 students or 55.56% in cycle 1 increased to 19 students or 70.37% and in cycle 2 to 24students or 88.89%. The Conclusion study shows "The use of Black Green Game can improve learningachievement basic motion run in Class 3 SD Negeri 01 Sirangkang Academic Year 2013/2014 can be used asa picture and enter for teachers on innovative teaching methods tailored to the characteristics of the students.